Framing a Brazilian singer and activist: asymmetries between Portuguese cultural coverage and TikTok - Scalabrin Müller, Mariana; Gravato, Davide (AoIR Selected Papers of Internet Research, 2026)
This paper explores the differences between traditional cultural coverage and digital media-relevant content. We focus on how the Brazilian singer and activist Linn da Quebrada is portrayed in the Portuguese newspaper $2 and on TikTok. Brazil and Portugal have had a relationship since the colonial period in the sixteenth century. The common language (Portuguese) and digital media habits allow a flux of cultural products between the two countries. However, there is a gap in studies that analyze them considering the colonial context. Previous studies identified the Portuguese cultural coverage as aligned with the country’s cultural industries and elites, with little space for decolonial perspectives and issues such as racism, sexism, and transphobia. The Brazilian singer and activist Linn da Quebrada is an exception in this scenario: the only trans person featured two times in the Portuguese newspaper Público in 2018. Her work was linked to the Brazilian political context and presented as a leading force in feminist and queer movements. Seven years later, we analyzed 24 news pieces published in $2 (2019-2024) mentioning Linn da Quebrada, identifying four thematic axes. In the second stage, through netnography, we analyzed 16 top-ranked videos and 2043 comments associated with them. Findings indicate asymmetries between themes and narratives circulating Linn da Quebrada in Portugal. News pieces predominantly feature the idea of a trans/feminist Brazilian icon. On TikTok, themes are more diverse, including interviews, performances, participation in a reality show, and instances of hate speech in user comments.